Brussels Declaration: a vehicle for the advancement of tobacco and alcohol industry interests at the science/policy interface? - McCambridge, J.; Daube, Mike; McKee, M. (BMJ Publishing Group, 2018)
The case for policies to be based on evidence appeared to gain a major boost with the publication of the Brussels Declaration, apparently with support from many leading scientists and institutions. Yet, as we show in this analysis, there are major concerns about how it was developed and, in particular, the extensive involvement of tobacco and alcohol industry actors. We describe how its coverage of conflicts of interest and vested interests is consistent with the perspectives of these same actors. The process of developing the Declaration successfully involved science advisors, other senior officials in governments and politicians in its preparation. Despite this, the final Declaration fails to address the need for safeguards to protect the integrity of science or policy from corporate interests, including in relation to the tobacco industry. This undermines Article 5.3 of the Framework Convention on Tobacco Control which seeks to protect public health policies from interference by the tobacco companies. More broadly, the Declaration offers potential to serve as a vehicle for advancing the vested interests of corporate sectors in public policymaking and appears to have been regarded in this way by a range of organisations related to the alcohol industry. This exercise is now being extended to the continent of Africa, which is strategically important to both the tobacco and alcohol industries. It will be important to study carefully to what extent initiatives like this form part of the global political strategies of tobacco and alcohol industry actors.